The Role of Life-History and Ecology in the Evolution of Color Patterns in Australian Chrysomeline Beetles - Tan, Eunice J.; Reid, Chris A. M.; Symonds, Matthew R. E.; Jurado-Rivera, José A.; Elgar, Mark A. (Frontiers in Ecology and Evolution, 2017)
The variation in animal coloration patterns has evolved in response to different visual strategies for reducing the risk of predation. However, the perception of animal coloration by enemies is affected by a variety of factors, including morphology and habitat. We use the diversity of Australian chrysomeline leaf beetles to explore relationships of visual ecology to beetle morphology and colour patterns. There is impressive colour pattern variation within the Chrysomelinae, which is likely to reflect anti-predatory strategies. Our phylogenetic comparative analyses reveal strong selection for beetles to be less distinct from their host plants, suggesting that the beetle colour patterns have a camouflage effect, rather than the widely assumed aposematic function. Beetles in dark habitats were significantly larger than beetles in bright habitats, potentially to avoid detection by predators because it is harder for large animals to be cryptic in bright habitats. Polyphagous species have greater colour contrast against their host plants than monophagous species, highlighting the conflict between a generalist foraging strategy and the detection costs of potential predators. Host plant taxa – Eucalyptus and Acacia – interacted differently with beetle shape to predict blue pattern differences between beetle and host plant, possibly an outcome of different predator complexes on these host plants. The variety of anti-predator strategies in chrysomelines may explain their successful radiation into a variety of habitats and, ultimately, their speciation.